Polemik Al-WarrÄq dengan Nestorian, Yakobit, Melkit Kajian Perjumpaan Kristologi Kristiani dan Islami - , DIDIK CHAHYONO WIDYATAMA, Prof. Dr. JB Banawiratma ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Muslims and Christians in Indonesia havestruggled in communicating faith in the new context of religious plurality. AbÅ« IsÄ al WarrÄq and the three Christian communities, Nestorians, Jacobites, and Melkites, are among pioneers in finding appropriate ways to communicate faith in a world characterized by religious diversity. The questions I am to answer are : What are AbÅ« IsÄ al WarrÄqâs objections against Christologies formulated by Christian Nestorians, Jacobites, and Melkites? What are supporting and unsupporting factors in their Christological polemics? With the failure doctrinal mode in communicating faith, what kind of alternative approach that allows Muslims and Christians to learn from each otherâs christological reflection? To answer these questions, I review the works of AbÅ« 'IsÄ al-WarrÄq. He engaged in Christological polemics against Christian Nestorians, Jacobites, and Melkites. The objection of Al-WarrÄq towards Christology because his excessive emphasis on rationality. Al-WarrÄq argued that the concept of unity between the divine and the human nature in Christ formulated by these communities was complex, contradictive, and illogical. His Islamic tradition that absolutely distinguishes God from humans, influenced his critical questions against them. I analyze a number of factors of the polemic Christology that makes it difficult to have inter-religious dialogue. 1) Christological polemic underway with doctrinaire approach. The religious communities difficultly involved in communicating each other because each of them strictly adhered to the official teachings of religion. 2) Another factor, Christological polemic is difficult to understand due to cultural differences in ways of thinking between Muslim and Christian communities. 3) In addition, the development of language and terms that vary from era to era and the influence of traditional theology, have contributed to complicate the polemic Christology. 4) Factor that increasingly emphasizes the difficulty in polemics Christology is the attempt to blame the teaching of other religions. After understanding and analyzing their Christological polemics, I offer an alternative Christology to help Muslims and Christians in building communication of faith such as, Christ as mediator, Jesus as messenger of God, Jesus as compassionate person to human problem, Jesus as a true friend. I owe debts from both Muslim and Christian thinkers in formulating it. My intense involvements in interfaith dialogue shape my Christological reflection. Through this research, I am aware that religious communities in Indonesia, especially Muslims and Christians, need to formulate Christology informed by interfaith dialogue. This new Christology goes beyond confrontational and doctrinal models. By fostering mutual respect between Muslims and Christians, we can expect that they learn about the religious othersâ faith and deepen their own faith.